National drug utilization trend of analgesics in China: an analysis of procurement data at 793 public hospitals from 2013 to 2018 - Honghao Shi; Xianwen Chen; Xueli Liu; He Zhu; Fei Yu; Carolina Oi Lam Ung; Wai Sin Chan; Hao Hu; Sheng Han (Taylor & Francis Group, 2021)
Background This research aimed to evaluate analgesic utilization in public hospitals from 2013 to 2018 by analyzing the procurement data of 793 hospitals in China. Methods This study applied a retrospective observational study by using a database of the Chinese Pharmaceutical Association. The final dataset covers 30 provinces and municipalities in China, with a total of 793 public hospitals with complete procurement records of analgesics from January 2013 to December 2018. Procurement cost and dosage utilization were analyzed through descriptive trend statistics. Results From the procurement cost data, analgesics mainly consisted of opioids and non-steroidal anti-inflammatory drugs (NSAIDs), and the annual cost of both types of drugs increased yearly. The 6-year total cost of opioids accounts for 57% (17,800 million CNY), followed by the cost of NSAIDs accounts for 37% (11,400 million CNY). From 2013 to 2018, the annual cost of opioids nearly doubled, while the annual cost of NSAIDs doubled. The total 6-year clinical drug dosage of opioids accounts for 45% (675 million total defined daily dose (DDD)), and the NSAIDs account for 50% (747 million total DDD). From 2013 to 2018, the annual clinical drug dosage of NSAIDs increased by about 0.6 times. The annual clinical drug dosage of opioids has more than doubled. The top three opioid drugs were dezocine injection, remifentanil injection, and sufentanil injection solution. the top three NSAIDs were flurbiprofen injection, parecoxib injection, and celecoxib oral solution. Conclusion In China, analgesics utilization increased rapidly at public hospitals from 2013 to 2018. The utilization of analgesics was highly concentrated in NSAIDs and opioids. Within the two types of analgesics, the main analgesics utilization is also highly concentrated, with some highly risky analgesics. The rational guideline for the utilization of analgesics needs to be established with the support of real-world evidence.